Supramolecular Protein Assembly Retains Its Structural Integrity at Liquid–Liquid Interface. Issue 4 (13th January 2020) - Sarker, Mridul; Lee, Hwankyu; Gonçalves, Rui A.; Lam, Yeng Ming; Su, Haibin; Lim, Sierin
Abstract: Adsorption of globular proteins at liquid–liquid interface results in compromised structures and functionalities to maintain a thermodynamically favorable state. However, the structural behavior of highly symmetrical supramolecular protein assemblies, adsorbed at the liquid–liquid interface, is not well understood. In this study, a model supramolecular protein assembly, E2 protein nanocage, a dodecahedral cage‐structured protein, is studied upon adsorption at the oil–water interface by both theoretical and experimental analyses. Molecular dynamics simulations and force estimation reveal that noncovalent interactions between E2 subunits dominate over the tangential force experienced by E2 at the interface allowing it to retain its structural integrity. Experimental analyses confirm the adsorption of E2 on the liquid–liquid interface with negligible penetration depth. Molecular structural analyses further suggest the structural integrity of the caged structure of E2 at the oil–water interface with minimal change in the tertiary and secondary structures. In conclusion, this study brings new insights into the behavior of highly symmetrical supramolecular protein assemblies at liquid–liquid interface which is important in preserving their functionalities. Abstract : This article reports in‐depth theoretical and experimental analyses of structural integrity of supramolecular protein assembly at liquid‐liquid interface. The retention of the structural integrity of a model supramolecular protein assembly, E2 protein nanocage, at oil‐water interface is attributed to the dominating stabilizing forces between the subunits over tangential force experienced at the interface.